BASELINE SURVEY ON ENDOPARASITIC FAUNA OF THE SILVER CATFISH (Chrysichthys nigrodigitatus) FROM ESCRAVOS ESTUARY, DELTA STATE NIGERIA, AND ITS ZOONOTIC IMPLICATION FOR FISH CONSUMER’S HEALTH - Michael, Amaka; Eyo, Victor O.; Eriegha, Ochuko Joshua (FUDMA JOURNAL OF SCIENCES, 2024)
The Silver Catfish (Chrysichthys nigrodigitatus) is one of the important food fishes for the inhabitants of the Escravos Estuary. Due to lack of information on the parasites of fish species in the Escarvos Estuary, including C. nigrodigitatus, fish eaters from the Escravos Estuary are at grave danger of contracting zoonotic diseases.  The purpose of this study was to determine the prevalence of endoparasites in the Silver Catfish (Chrysichthys nigrodigitatus) from the Escravos Estuary, Nigeria. A total of 180 samples of C. nigrodigitatus were collected from September 2023 to February 2024 from fish landing sites in Okerenkoko community. The fish samples were transported to Fisheries and Aquaculture Laboratory, Nigeria Maritime University, Okerenkoko for examination and endoparasites identification. Two genera of endoparasites were found that infect C. nigrodigitatus from the Escravos Estuary, namely Procamallanus laevionchus and Pomphorhynchus laevis belonging to nematode and acanthocephalan. Only 6 samples were infected with 12 endoparasites with a total prevalence of 3.33 %. More hosts were infested with more parasites in the rainy season than dry season with a rainy season prevalence of 4.17 % and 1.17 % for dry season. Prevalence (6.25 %) of endoparasites was higher in 40.0 – 49.9 cm size class than other length classes with 20.0 – 29.9 cm size class recording the least prevalence (1.67%). More female hosts (66.67%) were infested than male hosts (33.33 %). Parasites were only found in the intestine and stomach of C. nigrodigitatus with no parasite in the fillet, liver, heart, and kidney. In conclusion,...
Keywords: Endoparasites; Escravos Estuary; Zoonosis; Chrysichthys nigrodigitatus; Prevalence; Intensity